Avaliação da sintomatologia afetiva e cognitiva de adolescentes epilépticos - Stela, Florindo [UNESP] (My University, 1996)
The present work aimed to study the relationship between epileptic condition and psychological activity. The purpose of this investigation was to identify cognitive complaints and affective disturbs, like depressive disorders, and to compare both with epileptic condition. Forty epileptic adolescents, aged from 13 to 19 years old were analyzed. These patients were a consecutive series of males and females attending the Neuroepilepsy Center from the Universidade Estadual de Campinas, SP, and from lower social-economic background. The methodological procedures included specific questionnaires (a open and a assertive kind), and the Zung Self-rating Depression Scale. Cognitive alterations like thinking slowness or memorizing complaints in many patients, and affective disorders like depressive disturbs in 82.5% were the basic findings. The results also showed association between frequency of seizures and depressive disturbs; and between chronicity of epileptic condition and depressive disturbs. The discussion of these data suggests a relationship of epileptic condition with psychological reactions. We concluded that it is necessary to elevate the self-concept of these depressive patients in order to reduce their psychic suffering.
Evaluation of affective and cognitive symptoms in epileptic adolescents
Keywords: Epilepsy; Mental health; Psychological symptoms